Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702154
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Mobile Food Journal

Abstract: Food choices are among the most frequent and important health decisions in everyday life, but remain notoriously difficult to capture. This work examines opportunities for lightweight photo-based capture in mobile food journals. We first report on a survey of 257 people, examining how they define healthy eating, their experiences and challenges with existing food journaling methods, and their ability to interpret nutritional information that can be captured in a food journal. We then report on interviews and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…Congruent with the rise of consumer health technologies, HCI research has increasingly examined the use of personal informatics tools [2] involving physical activity [27,30], food intake [15,16], sleeping behaviour [52], productivity [13], mental wellness [34], menstrual cycles [23], disease progression [3] and care-giving [63]. Rooksby et al [15] characterise these self-tracking practices as 'lived' -enmeshed in everyday life -and identify overlapping selftracking styles, such as documentary tracking and diagnostic tracking.…”
Section: Self-tracking With Personal Informatics Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Congruent with the rise of consumer health technologies, HCI research has increasingly examined the use of personal informatics tools [2] involving physical activity [27,30], food intake [15,16], sleeping behaviour [52], productivity [13], mental wellness [34], menstrual cycles [23], disease progression [3] and care-giving [63]. Rooksby et al [15] characterise these self-tracking practices as 'lived' -enmeshed in everyday life -and identify overlapping selftracking styles, such as documentary tracking and diagnostic tracking.…”
Section: Self-tracking With Personal Informatics Systemsmentioning
confidence: 99%
“…Rooksby et al [15] characterise these self-tracking practices as 'lived' -enmeshed in everyday life -and identify overlapping selftracking styles, such as documentary tracking and diagnostic tracking. While Elsden et al [19] have provided a design perspective on documentary tracking, highlighting self-expression and remembering, Karkar et al [32] have examined diagnostic tracking in the context of detecting individualised food triggers in irritable bowel syndrome.…”
Section: Self-tracking With Personal Informatics Systemsmentioning
confidence: 99%
“…Recent automated food recognition technologies rely on wearable cameras or phones to capture food photos and leverage computer vision techniques to analyze food ingredients [65,66]. Another alternative method is to use an in-the-moment photo as a lightweight food journal to reduce user effort [67]. Future research should consider these more advanced self-tracking methods to reduce participation attrition as well as increase the accuracy and usefulness of self-tracked information.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing ease of tracking one own's data, continued engagement with self-tracking technology is not likely to persist long term unless the issues of individual motivation, incentives, and habit formation are also addressed. Recent findings [6,8] have revealed that a vast number self-tracking technology adopters eventually lost their interest in self-tracking over time, leading to reduced compliance and increased abandonment rate. Many users tended to use the self-tracking data for short-term goals and migration between tools was fairly common [28].…”
Section: Introductionmentioning
confidence: 99%
“…To promote continued engagement with self-tracking health technologies, various financial and non-financial incentive designs have been proposed. For example, the designs of self-tracking applications can be improved by providing more meaningful behavioral insights from the data [6,8] and improving social sharing to support observational learning [6]. In the context of randomized health intervention trials, financial incentives have been commonly used to motivate health behavior changes and promote self-tracking compliance [15,25].…”
Section: Introductionmentioning
confidence: 99%